Mobile Game â€œColor in Lifeâ€ Development for Dichromatism Color Blind - Ivan Reinaldo; Boy Nurttjahyo Moch (Journal of Games, Game Art, and Gamification, 2019)
The purpose of this research was to escalate playersâ€™ knowledge on color blindness by designing an educational video game which design was oriented to dichromatism color blind. The topic selection was based on the lack of playersâ€™ deeper knowledge on color blindness. The graphic and gameplay selection on this research was adjusted to the chosen color blind category. Research methods were conducted by analysis, development, and evaluation. Analysis was done by questionnaire. Development was done by game design document, UML, storyboard, and was implemented using Unity. Evaluation on 35 players, which are 32 with normal eyes and 3 with color blindness, was done by two approaches, which are t-test and questionnaire. The result of t-test was t(34) = -7.704, p < 0.05 and Enjoyment score on CEGE is 0.763 for normal eyes and 0.651 for colorblind. To conclude, there was an improvement on knowledge from the video game and the design was enjoyable.